Ventricular Septal Rupture (VSR) in Post-Acute Anterior Myocardial Infarction Patients : A Case Series - Ken Christian Kawilarang; I Kadek Herry Hermawan; Febryanti Hartono (Cardiovascular and Cardiometabolic Journal, 2022)
Case Summary: We present 2 cases of post-STEMI VSR. They had anterior AMI without reperfusion therapy because of patient delay and limited resources. Thereafter apical VSR occurs on 5th day. VSR was suspected because of sudden hemodynamic deterioration and new holosystolic murmur (Grade III/VI) at left parasternal line of fourth-fifth ICS. Then it was confirmed by echocardiography. Both patients underwent hemodynamic stabilization while waiting for surgical therapy. Unfortunately, they deceased because of cardiogenic shock accompanied by other comorbidities. Discussion: VSR causes shunt from left to the right ventricle, which overloads the RV, leading to cardiogenic shock. The peak incidence of VSR in the first 24 hours or 3-5 days post-AMI. This fits both of our cases. VSR occurs in total coronary occlusion, which then causes coagulation necrosis in the ischemic area, characterized by neutrophils that trigger apoptosis and lytic enzymes, so that septum becomes thin, brittle then ruptures. VSR is most common in anterior AMI and the defect is at apical septum, as in our patients. Definitive therapy for VSR is surgical closure, but the best timing is still under debate. This article is expected to make us more aware of post-AMI VSR, so we can quickly diagnose and promptly treat the patients with multidisciplinary approach. This is very important to optimize patient’s outcomes even in limited resources area.